Hamsun’s “mal du siècle”: (Re)reading Pan through Chateaubriand's René - Conner, Tom (Nordlit, 2020)
My paper expands on several conference themes, specifically “geographical places” and “boundaries,” and will explore the elasticity and intertextual implications of both terms as they apply to national literatures and writers, as well as their porous nature in literary studies (including theory, history, and criticism, according to René Wellek’s classic and still widely accepted triptych of literary studies [Wellek x]). Specifically, I will examine the resonance of the Romantic malaise known in France as “le mal du siècle” and how it might inform a reading of Knut Hamsun’s novel Pan (1894) and shed light on the more than eccentric behavior of its main character, Lieutenant Glahn. The French Romantic writer Chateaubriand (1768-1848), whose slender novel René (1802), with which “le mal du siècle” is most closely associated, represents the epitome of the Romantic hero, who evidently had not drawn his last breath when Hamsun published Pan almost one century later. Upon a closer reading of the two novels, there is more than enough to warrant a comparison. Glahn and René are archetypes of a similar malady afflicting overly sensitive, generally upper-class young men of a nervous and indeed neuroticdisposition.
Keywords: Crisis of comparative literature; Hamsun; Chateaubriand; Pan; René; “mal du siècle .ˮ